2016
DOI: 10.12659/msm.898177
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Luteolin on Lipopolysaccharide-Induced Acute Renal Injury in Mice

Abstract: BackgroundSepsis can cause serious acute kidney injury in bacterium-infected patients, especially in intensive care patients. Luteolin, a bioactive flavonoid, has renal protection and anti-inflammatory effects. This study aimed to investigate the effect and underlying mechanism of luteolin in attenuating lipopolysaccharide (LPS)-induced renal injury.Material/MethodsICR mice were treated with LPS (25 mg/kg) with or without luteolin pre-treatment (40 mg/kg for three days). The renal function, histological change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 35 publications
2
24
0
Order By: Relevance
“…The expression of this cytokine matches well with the behavior of IL-1 and, although no studies have been reported covering the effects after exposures to carbon-based nanomaterials, lowered expression of this cytokine was observed in rheumatoid arthritis patients after the exposures to anti-rheumatic drugs 47 . A similar effect has been documented in mice, where the induction of acute renal injury was protected by the bioactive flavonoid Luteolin, showing anti-inflammatory and renal protection effects 48 .…”
Section: Discussionsupporting
confidence: 65%
“…The expression of this cytokine matches well with the behavior of IL-1 and, although no studies have been reported covering the effects after exposures to carbon-based nanomaterials, lowered expression of this cytokine was observed in rheumatoid arthritis patients after the exposures to anti-rheumatic drugs 47 . A similar effect has been documented in mice, where the induction of acute renal injury was protected by the bioactive flavonoid Luteolin, showing anti-inflammatory and renal protection effects 48 .…”
Section: Discussionsupporting
confidence: 65%
“…NF-κB activation associated with increased ROS generation is pivotal in the consequent expression of pro-inflammatory cytokines like TNF-α. These chemokines may then facilitate migration and infiltration of inflammatory cell and a secondary wave of ROS generation, and further amplify the inflammatory cascade and injury [62]. In another way, paricalcitol weakens renin and angiotensin II expression in VDR knockout mice [63], telling that paricalcitol inhibits renal inflammation by overwhelming the RAAS, as angiotensin II is a known pro-inflammatory stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB activation associated with increased ROS generation is pivotal in the consequent expression of proinflammatory cytokines like TNF-α. These chemokines may then facilitate migration and infiltration of inflammatory cell and a secondary wave of ROS generation, and further amplify the inflammatory cascade and injury [43]. In another way, paricalcitol weakens renin and angiotensin II expression in VDR knockout mice [44], telling that paricalcitol inhibits renal inflammation by overwhelming the RAAS, as angiotensin II is a known proinflammatory stimulus.…”
Section: Discussionmentioning
confidence: 99%